The new majority : toward a popular progressive politics - Greenberg, Stanley B., 1945-; Skocpol, Theda (Yale University Press, 1997)
In an era of widespread and unsettling change in families, businesses, and communities, most Americans yearn for a government that will take their side. The contributors to this bold and visionary book argue that America is ready for a progressive politics with substance and bite. They contend that by embarking on a popular progressive course, the Democratic Party can become the moral voice and practical partner of American families striving for a better life. This provocative book is a dialogue among Stanley B. Greenberg, Theda Skocpol, and other well-known thinkers. They reject conservative answers to America's most pressing problems - fraying social ties, hard-pressed families, sluggish economic growth, and widening gaps between the circumstances of the most privileged and those of everyone else. They urge a renewal of the nation's social contract, explain how to revitalize American democracy.